SOCIAL PERCEPTIONS AND ATTITUDES TOWARDS WASTE MANAGEMENT - Maral Bold, (International Journal of Innovative Technologies in Social Science, 2025)
As the global population grows, an abundance of products are being produced to fulfill endless demands, leading to a corresponding rise in waste and associated challenges. Waste sorting is the most efficient method to decrease waste volume, and addressing waste-related issues requires universal recognition of the significance of waste sorting and its integration into daily routines - recycling waste and repurposing items that may be unwanted by some but valuable to others. Waste education is crucial in raising awareness about the importance of reducing, reusing, and recycling waste.This study explores public perceptions and attitudes toward waste management in Mongolia, focusing on Ulaanbaatar. The increase in waste generation due to population growth, urbanization, and industrialization has made effective waste management a crucial issue.The research examines citizen’s awareness, knowledge, and practices related to waste sorting and recycling using survey data. Results show that majority of respondents sometimes sort their waste, while some of them do not sort at all, indicating limited awareness and infrastructure challenges. A majority of participants rated Ulaanbaatar's waste management as poor, but most of them acknowledged recycling as an effective waste processing method.The study highlights gaps in education and information dissemination, with more than sixty present of citizens reporting minimal exposure to waste separation education. The study underscores the need for early childhood education on waste management, ongoing training for citizens and producers, targeted information campaigns, and increased public involvement to establish sustainable waste management practices.Recommendations include improving waste collection infrastructure, implementing educational programs, and promoting community participation in waste management planning.